24-Epibrassinolide, a Phytosterol from the Brassinosteroid Family, Protects Dopaminergic Cells against MPP+-Induced Oxidative Stress and Apoptosis - Julie Carange; Fanny Longpré; Benoit Daoust; Maria-Grazia Martinoli (Journal of Toxicology)
Oxidative stress and apoptosis are frequently cited to explain neuronal cell damage in various neurodegenerative disorders, such as Parkinson' s disease. Brassinosteroids (BRs) are phytosterols recognized to promote stress tolerance of vegetables via modulation of the antioxidative enzyme cascade. However, their antioxidative effects on mammalian neuronal cells have never been examined so far. We analyzed the ability of 24-epibrassinolide (24-Epi), a natural BR, to protect neuronal PC12 cells from 1-methyl-4-phenylpyridinium- (MPP+-) induced oxidative stress and consequent apoptosis in dopaminergic neurons. Our results demonstrate that 24-Epi reduces the levels of intracellular reactive oxygen species and modulates superoxide dismutase, catalase, and glutathione peroxidase activities. Finally, we determined that the antioxidative properties of 24-Epi lead to the inhibition of MPP+-induced apoptosis by reducing DNA fragmentation as well as the Bax/Bcl-2 protein ratio and cleaved caspase-3. This is the first time that the potent antioxidant and neuroprotective role of 24-Epi has been shown in a mammalian neuronal cell line.